Igualdad de oportunidades: una aplicación al sistema tributario chileno - ejecutivo, editor (Estudios de Economía, 2016)
This work evaluates the fiscal distributive policy (tax and transfer payments) ofChile at the perspective of the Equality of Opportunities approach. Under thiscriterion it is desirable to compensate people by the circumstances in that theyare born but it is necessary to allow the differences originated in the individualeffort. The main conclusion is that the, in the Chilean case, the application ofthe equality of opportunities approach on the fiscal system leads to lower theincome marginal taxes rate and the worsening of the income distribution.